Identifying the Teaching Aid Effect That Parents Use to Enhance Reading Skill of Their Children - Mohamad Sharil, Muhammad Syazwan; Che Daud, Norhayati; Shaharudin, Haszlin (Idealogy Journal, 2022)
This research paper aims to identify the teaching aids that parents use to enhance reading for their children. At the beginning of every school session, few students in primary school in Malaysia will enrol in special recovery classes. Students in primary school will take a particular recovery class because they have a few problems in their studies, such as reading, writing, and calculating skills. The researcher will focus on parents' teaching aid to enhance their children's reading skills in this research. Base on a Utusan Malaysia at 19 th March 2019, Dr. Mahathir Mohamad say ‘Marilah jadikan sekolah kebangsaan hebat semula’. From these slogans, we can see that every primary school must upgrade their learning system to solve the students' problems in studies. Besides that, the parent must help the government to reach a goal. Parents can use teaching aids to teach their children, such as electronic, non-electronic teaching aids and other manual activities. The outcome of this research paper purposely will be helping the parents on how to teach their children using teaching aids and what the perfect teaching aid that parents can use to solve the reading problem. The study would benefit the education system to arrange the guild line for teachers to improve their teaching skills for students with reading problems. Keywords: Teaching Aids; Electronic Teaching Aids; Non-Electronic Teaching Aids; Activity; Parents; Reading Skills.